IDENTIFIKASI HAZARD ERGONOMI DI INSTALASI RADIOLOGI RSUD DR. SOESELO KABUPATEN TEGAL (Studi Kasus Pada Radiografer) - Nur Fadillah Amanda Masso; Sofie Nornalita Dewi (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT The radiology installation is a medical support unit with a high risk of ergonomic hazards due to radiographers’ work activities involving non-ergonomic postures, repetitive movements, and patient manual handling activities. These conditions have the potential to cause musculoskeletal disorders and reduce service quality. Based on conditions at the Radiology Installation of RSUD dr. Soeselo, the implementation of ergonomics in radiographers’ work activities has not been optimal; therefore, this study aimed to identify potential ergonomic hazards and their contributing factors. This study used a descriptive qualitative method conducted from October 2025 to April 2026 with research subjects consisting of 11 radiographers, the head of the installation, and the head of the unit. Data were collected through observation, interviews, documentation, and literature studies. The results showed that the main ergonomic hazards included bending postures, prolonged standing, and repetitive movements that caused complaints of lower back pain, shoulder pain, muscle soreness, and fatigue. The main contributing factors included the absence of ergonomic training, limited patient transfer aids, the unavailability of ergonomic standard operating procedures (SOPs), the use of heavy conventional equipment, and high workloads with shift systems. The implementation of ergonomics in the radiology installation has also not been carried out in a structured manner and has not been supported by routine evaluations. Therefore, it is necessary to develop ergonomic SOPs, conduct regular training, provide supporting equipment, and carry out routine evaluations to improve radiographers’ occupational safety and health. ABSTRAK Instalasi radiologi merupakan unit penunjang medis yang memiliki risiko hazard ergonomi tinggi akibat aktivitas kerja radiografer yang melibatkan postur tidak ergonomis, gerakan berulang, serta aktivitas manual handling pasien. Kondisi tersebut berpotensi menimbulkan gangguan muskuloskeletal dan menurunkan kualitas pelayanan. Berdasarkan kondisi di Instalasi Radiologi RSUD dr. Soeselo Kabupaten Tegal, penerapan ergonomi pada aktivitas kerja radiografer belum optimal sehingga penelitian ini bertujuan mengidentifikasi potensi hazard ergonomi dan faktor penyebabnya. Penelitian menggunakan metode deskriptif kualitatif yang dilaksanakan pada Oktober 2025–April 2026 dengan subjek penelitian sebanyak 11 radiografer, kepala instalasi, dan kepala ruang. Pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi, dan studi kepustakaan. Hasil penelitian menunjukkan bahwa potensi hazard ergonomi utama meliputi postur membungkuk, berdiri terlalu lama, dan gerakan berulang yang menyebabkan keluhan nyeri pinggang, nyeri bahu, pegal, dan kelelahan. Faktor penyebab utama meliputi belum adanya pelatihan ergonomi, keterbatasan alat bantu pemindahan pasien, belum tersedianya SOP ergonomi, penggunaan alat konvensional yang berat, serta beban kerja tinggi dengan sistem shift. Penerapan ergonomi di instalasi radiologi juga belum dilakukan secara terstruktur dan belum didukung evaluasi rutin. Oleh karena itu, diperlukan penyusunan SOP ergonomi, pelatihan berkala, penyediaan alat bantu, dan evaluasi rutin untuk meningkatkan keselamatan dan kesehatan kerja radiografer.